Pengaruh Stres Kerja, Disiplin Kerja, dan Kompetensi Terhadap Kepuasan Kerja Karyawan Kopi Kenangan di Cikarang Utara - Sabrina Luna Rahellea; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri; Dewi Puspaningtyas Faeni; Indah Rizki Maulia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of work stress, work discipline and competency on the job satisfaction of Kopi Kenangan employees in North Cikarang. The research method used is quantitative research which is used to examine certain populations and samples, data collection using research instruments, quantitative or statistical data analysis, with the aim of testing predetermined hypotheses. The sampling technique used was saturated sampling technique or the entire population was sampled, while the population in this study was 50 respondents. Data analysis using Smart PLS 3.0 software. Based on the results of the path coefficient hypothesis test, there are P-values ​​of > 0.000 or > 0.05 and the work stress t-statistics value has a value of 5.017 or > 1.96, so it is stated that there is a significant influence between the work stress variables on job satisfaction. Based on the results of the path coefficient hypothesis test, there is a value. The P-value is 0.011 or <0.05 and the work discipline t-statistics value is 2.541 or ≥1.96, so it is stated that there is a significant influence between the work discipline variable on job satisfaction. Based on the results of the path coefficient hypothesis test, there are P-values ​​of 0.043 or <0.05 and the competency t-statistics value has a value of 2.032 or >1.96, so it is stated that there is a significant influence between the competency variables on job satisfaction. The results show that the coefficient of determination (R Square) in the first substructure is 0.987, which means that simultaneously, the total influence of work stress, work discipline and competence on job satisfaction is 98.7%.